Qualitative analysis of gynecologic oncology patients' experience with treatment holidays - Benjamin Margolis; Megan E. Sutter; Leslie R. Boyd; Abigail Ford Winkel (Elsevier, 2022)
Objective: Patients with advanced or recurrent gynecologic malignancies occasionally take breaks from systemic treatment colloquially referred to as "treatment holidays" or "chemotherapy holidays." There are no data from the patient perspective that help describe this experience. Methods: Patients with recurrent or advanced primary gynecologic malignancies who had decided to enter a treatment holiday were recruited and interviewed. A treatment holiday was defined as a planned temporary break or delay in treatment for a patient with recurrent or advanced primary gynecologic malignancy for reasons other than pursuit of hospice or best supportive care, research protocol violation or unacceptable toxicity. Interviews were audiotaped, transcribed and then analyzed using an inductive thematic analysis. Results: Of 6 total patients identified for participation, 5 completed interviews with ages ranging from 57 to 80 years. Two participants returned to their previous treatment regimen after their holiday therapy, two switched therapies, and one remained on an extended break from systemic treatment. Treatment holidays were experienced as a break from the physical and psychological routine of being a cancer patient, but also brought about feelings of a lack of structure, uncertainty, and led to a confrontation with mortality issues. Overall, participants had favorable experiences which were initiated by their providers in whom they had a deep sense of trust. Conclusion: Patients experience treatment holidays as a positive and valuable break from the physical and psychosocial routine of cancer treatment and illness. These experiences produce distinct emotional needs that clinicians should address to best support patients electing treatment holidays.